Good Corporate Governance And Financial Performance Of Shariah Banks In Indonesia : Literature Review - Umi Nandiroh; Irma Hidayati; Vinna Anggraeni (Cita Konsultindo Research Center, 2023)
This essay review examines the relationship between corporate governance and financial performance in Islamic banking. It begins by defining corporate governance and its importance, followed by an explanation of the significance of financial performance in Islamic banking. The review then provides an overview of corporate governance principles and their application in Islamic banking, including a comparison of governance practices in Islamic banking and conventional banking. The essay also includes case studies of a prominent Islamic bank, examining its corporate governance practices and financial performance. The review discusses the factors that affect financial performance in Islamic banking and explores how corporate governance practices can affect financial performance in Islamic banking. It also explores how financial performance can impact corporate governance practices in Islamic banking. Finally, the review summarizes the key findings and implications for future research, as well as implications for practice in Islamic banking. The essay highlights the need for effective governance practices to enhance financial performance in Islamic banking and suggests future research directions, including longitudinal studies, comparative studies, and in-depth case studies. Overall, the essay emphasizes the importance of good governance practices in promoting financial stability and sustainability in Islamic banking.